Isolation of Fungi from Otitis Media patients in Erbil city - Ahmood, Asaad Abdel Jalil (Journal of medical and pharmaceutical sciences, 2017)
Although otitis media (OM) incidence estimates from around world widely, it is clear that OM is a very common childhood disease. It is especially prevalent in children younger than 2 years of age. Furthermore, the earlier the first episode of OM, the greater the risk of subsequent recurrent OM and chronic otitis media with effusion. In addition, a number of other host, agent, and environmental factors have been associated with increased risk of otitis media. Environmental factors that favor the transmission of upper respiratory pathogens increase the risk of OM, recurrent OM, and chronic OM with effusion. Several factors suggest a genetic role in OM susceptibility, which needs further exploration. Objectives: Isolation and identification of fungi from patients with chronic inflammation of the otitis media. Patients and Methods: A total of 50 samples were collected from patients with a clinical suspicion of Otomycosis, which was based on different clinical symptoms like pruritus, chronic otorrhea, Otalgia, impaired hearing. and on otoscopic findings like appearance of fungal mass or debris and blackish foul smelling discharge . It was a retrospective study conducted at Outpatient Department of ENT (Ear, Nose and Throat) of Erbil Teaching Hospital & Rezgary Hospital in Erbil city. Results: From 50 samples 23 (46%) were positive for fungus by using KOH exam & culture. Among positive patients, 13 (56.52%) were female and the rest 10 (43.48%) were male, candida and Aspergillus species were isolated from samples. Positive cases from females were more than positive male cases of patients and age range was from 20 yrs to 65 yrs. The highest number of positive cases were following in age group of 51-60 years old (47.82%), followed by 21-30 years age group (30.43%).